Plants: A natural solution to enhance raw milk cheese preservation?. (April 2020) - Dupas, Coralie; Métoyer, Benjamin; El Hatmi, Halima; Adt, Isabelle; Mahgoub, Samir A.; Dumas, Emilie
Graphical abstract: Highlights: Plants traditionally used in dairy products could be use as natural preservatives. Some plants used in dairy products have antimicrobial and antioxidant effect. Numerous plants extraction techniques exists and must be suitable for food industry. Current status on food legislation concerning raw milk and plant extract are reviewed. Commercial innovative systems developed with plant extracts are reviewed. Abstract: Plants have been traditionnally used for centuries in cheese manufacturing, either for their aromatic properties or as technological auxiliaries (e.g. milk-clotting enzyme preparations, cheese wrappers). Some of these plants are known to have antimicrobial and/or antioxidant properties and could also act as natural preservatives for raw milk and derived dairy products. This review examined the traditional uses of plants in dairy processing, and then focuses on known antimicrobial and antioxidant properties of their extracts (e.g. maceration, decoction, essential oil). Known effects of theses plants on technological flora (starter cultures and microorganisms implicated in cheese ripening) were also summarized, and the potential for plant extracts used in combination with hurdle technologies was explored. Then, legal restriction and bioactivity variations from a culture media to a food matrix was reviewed: non-toxic bioactive molecules found in plants, extract preparation modes suitable with foodgrade processing restrictions, the role of the food matrix as a hindrance to the efficiency of bioactive compounds, and a review of food legislation. Finally, some commercial plant extracts for milk preservation were discussed.